Sleep disturbance among Chinese survivors of childhood sexual abuse: associations with perceived discrimination and rumination - Wang, Wan; Wang, Xi (Frontiers in Psychiatry, 2025)
BackgroundAlthough childhood sexual abuse (CSA) has been widely recognized for its association with sleep disturbance (SD) in adulthood, little is known about its associations with perceived discrimination (PD) and rumination. This study seeks to build upon existing literature by examining the impact of CSA on adult SD within a Chinese survivor sample while also investigating the mediating effects of PD and rumination on this association.MethodsA total of 1,210 respondents completed the Childhood Sexual Abuse Questionnaire, the Inventory of Depressive Symptomatology Self Report, the Perceived Discrimination Scale, and the Ruminative Response Scale.ResultsParticipants with CSA experiences reported higher scores of SD and greater rates of insomnia and hypersomnia than those without such experiences (47.79% vs. 29.30%; 20.71% vs. 9.46%). CSA, SD, PD, and rumination were positively related with each other. CSA could predict SD not only directly but also indirectly through the mediating effects of PD and rumination.LimitationsDue to the cross-sectional design, the study is unable to demonstrate causality but, rather, that there exist important associations that are worth further investigation.ConclusionsThis study examined a sample of Chinese survivors of CSA to establish the link between CSA and adult sleep disturbances (SD). Our findings not only confirm this association but also shed light on the intermediary roles of PD and rumination in shaping this relationship. It suggests that interventions designed to mitigate the sense of discrimination and to foster the adoption of positive coping strategies could be instrumental in enhancing the sleep quality of those who have been sexually abused in their childhood.